REMEDIAL TEACHING SEBAGAI SUATU SOLUSI: Suatu Analisis Teoritis - Masbur Masbur (Jurnal Ilmiah Didaktika, 2012)
Teaching learning process is a two-sided process which occures significantly. It will run well if teachers could give positive influence to their students based on their level of competency. In general, the influence covers cognitive, affective, and psychomotoric aspects. To have an effective process of teaching, teachers should be skillful in using appropriate method, media, and evaluation as well as all the supporting elements to make the intercative process could occur in the classroom. In teaching learning process, teacher should play active roles, so does students. In the classroom, teacher often face many problems, among others, there are still students who are lack of understanding to the material taught. Related to that, teacher should do remedial to the students aiming at diagnosing the students’ problem in mastering the concept. By doing so, they would know whether the instructional tools, or method, media, and evaluation technique are not appropriate to their students. From the literature review done , it is found that teachers should do the remedial teaching to their students. Besides, in order to set an active, creative, innovative, and fun teaching learning situation, teachers should have some competencies.